FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN TRANSPORTASI UMUM BUS TRANS METRO DEWATA DENGAN METODE REGRESI LOGISTIK BAYES - DARMAYANTI, NI KADEK FENI; SUMARJAYA, I WAYAN; SUSILAWATI, MADE (E-Jurnal Matematika, 2024)
Transportation is very important in supporting people's daily mobility. The increasing population density has resulted in a high level of mobility that requires various modes of transportation, especially in urban areas, giving rise to the problem of traffic congestion. One alternative to reduce the level of congestion is to use public transportation that has been pursued by the government such as the Trans Metro Dewata bus. However, the use of this transportation bus is still quite low. Therefore, this study aims to determine what factors influence people to use the Trans Metro Dewata bus using the Bayes logistic regression method. The sampling method used was purposive sampling of 100 respondents with the criteria of people who live in the Sarbagita area (Denpasar, Badung, Gianyar, and Tabanan). The results obtained are the variables of travel purpose or destination, bus stop accessibility, and ownership of transportation modes have a significant effect on the use of the Trans Metro Dewata bus.